Flexible human-applicable infrared camouflage materials with temperature and emissivity tunability. (1st March 2023) - Chen, Junyu; Zhang, Shixian; Wei, Yuhao; Yi, Juan; Pang, Weitao; Zhang, Haoyue; Fu, Yuheng; Li, Chenjian; Xia, Wenlai; Xiong, Chuanxi
Abstract: Infrared stealth technology plays a vital role in development of defense industry and new military equipment. Infrared stealth materials with adjustable temperature and emissivity have potential applications in adaptive thermal camouflage. We used thermoplastic polyurethane (TPU) encapsulated with ionic liquid as the intermediate layer and graphene as the outer layers to prepare the infrared thermal camouflage composite material with adjustable temperature and emissivity. The ionic liquids with wide phase change transition temperature range from −40 to 37 °C could absorb heat from human body and keep the actual temperature of the surface of the composite film constant, due to their high latent heat during phase change process. Moreover, the infrared emissivity of graphene outer layer could be controlled by the intercalation of ionic liquids via applied electric field, which further achieves the thermal camouflage of the composite film. Under the continuous heating of heat source close to the body temperature, the obtained composite film shows a tunable thermal camouflage temperature range of 33 to 28 °C through the detection of an infrared camera, and the emissivity decreases 0.26. The obtained composite film has excellent mechanical properties could effectively realize the on-body infrared stealth, which provides constructive suggestions for the application of adaptive thermal camouflage such as new military equipment. Graphical abstract: MLG/PCILs with adjustable temperature and emissivity and has excellent mechanical properties which could effectively realize the on-body infrared stealth. Image 1 Highlights: PCILs can absorb body heat and joule heat. MLG/PCILs with adjustable temperature and infrared emissivity.